Case report: Absent fluorodeoxyglucose uptake in a dog with unexpected brain death - Koo, Yoonhoi; Na, Yejin; Yun, Taesik; Chae, Yeon; Lee, Dohee; Kim, Hakhyun; Yang, Mhan-Pyo; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2022)
A 5-year-old male Maltese dog was presented with generalized tonic seizures and hypermetria. Multiple nodular subcortical cerebellar enhancements and meningeal enhancement were observed on magnetic resonance imaging. Fluorodeoxyglucose-positron emission tomography/computed tomography was performed due to suspicion of neoplastic disease, and no fluorodeoxyglucose uptake was observed in the intracranial structures. In PET images of this dog, absent fluorodeoxyglucose uptake was identified in the brain indicating no cerebral metabolism, strongly suggested brain death. The dog had no spontaneous breathing and no brainstem reflexes for more than 24 hours after the termination of anesthesia. Through these results, this dog was diagnosed with unexpected brain death, and it is presumed that the cause was anesthesia. We report herein a case of brain death in a dog diagnosed using fluorodeoxyglucose-positron emission tomography/computed tomography.